2018
DOI: 10.1038/s41593-018-0231-0
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired perceptual learning in a mouse model of Fragile X syndrome is mediated by parvalbumin neuron dysfunction and is reversible

Abstract: To uncover the circuit-level alterations that underlie atypical sensory processing associated with autism, we adopted a symptom-to-circuit approach in the Fmr1-knockout (Fmr1) mouse model of Fragile X syndrome. Using a go/no-go task and in vivo two-photon calcium imaging, we find that impaired visual discrimination in Fmr1 mice correlates with marked deficits in orientation tuning of principal neurons and with a decrease in the activity of parvalbumin interneurons in primary visual cortex. Restoring visually e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
150
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(185 citation statements)
references
References 44 publications
12
150
1
Order By: Relevance
“…Recent studies have provided evidence for perceptual learning or discrimination deficits in Fmr1 knockout mice in both the tactile and visual domains . Although fewer studies have examined auditory perceptual learning in FXS models, there is evidence for impaired auditory‐cued fear conditioning in Fmr1 knockout mice .…”
Section: Audition‐associated Behavioral Changes In Fxsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have provided evidence for perceptual learning or discrimination deficits in Fmr1 knockout mice in both the tactile and visual domains . Although fewer studies have examined auditory perceptual learning in FXS models, there is evidence for impaired auditory‐cued fear conditioning in Fmr1 knockout mice .…”
Section: Audition‐associated Behavioral Changes In Fxsmentioning
confidence: 99%
“…Recent studies have provided evidence for perceptual learning or discrimination deficits in Fmr1 knockout mice in both the tactile 161,162 and visual domains. 163 Although fewer studies have examined auditory perceptual learning in FXS models, there is evidence for impaired auditory-cued fear conditioning in Fmr1 knockout mice. 164,165 It is not clear, however, whether this impairment is more cognitive than perceptual in nature, because Fmr1 knockout mice exhibit impairment on a variety of associative learning paradigms that are not dependent on auditory cues.…”
Section: Perceptual Learning and Decision Makingmentioning
confidence: 99%
“…However, little direct evidence for this hypothesis has been measured from identified excitatory and inhibitory neurons during quantifiable behavioral impairments. One recent study found that inhibitory neurons are more perturbed than excitatory neurons in superficial cortical layers 2/3 (L2/3) in a Fragile X syndrome mouse model of ASD (Goel et al, 2018). However, another study of ASD model mice observed reduced and poorly coordinated excitatory activity in frontal cortex of CNTNAP2 -/-KO mice (Lazaro et al, 2019), but these excitatory activity deficits were not measured during sensory impairments or behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our findings suggest that altered processing in distinct SF channels might contribute to altered visual perception and learning in FX and autism. that sensory alterations may be predictive of social communication deficits later in life in autism (Boyd et al, 2010;Turner-Brown et al, 2012).Both human and animal studies provide evidence that there is impaired information processing in early sensory areas in both autism and FX (Goel et al, 2018;Rais et al, 2018). Sensory hypersensitivity and reduced adaptation to sensory stimuli are some of the hallmark perceptual impairments in autism.…”
mentioning
confidence: 99%
“…Both human and animal studies provide evidence that there is impaired information processing in early sensory areas in both autism and FX (Goel et al, 2018;Rais et al, 2018). Sensory hypersensitivity and reduced adaptation to sensory stimuli are some of the hallmark perceptual impairments in autism.…”
mentioning
confidence: 99%